PP69 Supporting Decision Making: A Health Technology Assessment Training Proposal for Decision Makers. (23rd December 2022) - Faraldo-Valles, Maria-Jose; Varela-Lema, Leonor; Perez-Rios, Monica
Abstract : Introduction: Health technology assessment (HTA) reports are complex technical documents that address multiple aspects of the incorporation of a technology into the healthcare system applying complicated methodologies coming from different disciplines. The purpose of HTA is to support decision makers, who should have an adequate level of training to fully understand these assessments. However, most HTA education programs and courses are intended for HTA doers and there is a lack of practical guidance training aimed at preparing health managers or policy makers in HTA. The objective is to describe an HTA training program developed for decision makers of the three levels (health care administration, hospital management and clinical practice). Methods: The education program has been designed through a collaboration between the Public Health Department of the Faculty of Medicine of the University of Santiago de Compostela (USC) and the Galician Health Technology Assessment Agency that belongs to the Spanish HTA Bodies Network. The duration of the course is 200 hours and the methodology will be distance learning, through the virtual classroom of the USC. The teaching collaborators come from the academic field and the HTA area. Results: The course will cover the legal, clinical and organizational framework in which the HTA is developed in Spain and in Europe; and will approach the methodology used in HTA. The course is structured in six modules: (i) Research, development and regulation of health technologies; (ii) Role of HTA as a decision support tool; (iii) HTA Methodology; (iv) Health information systems (including use of real world data); (v) Incorporation of HTA into society (stakeholders); (vi) Future challenges (personalized medicine and e-health). Conclusions: A specific training about HTA from a practical approach not theoretical could be of interest for different stakeholders involved in the decision-making process across the health systems. This type of educational program will allow decision makers to have a good understanding of the wide range of information they handle.